Sapitinib Reverses Anticancer Drug Resistance in Colon Cancer Cells Overexpressing the ABCB1 Transporter - Gao, Hai-Ling; Gupta, Pranav; Cui, Qingbin; Ashar, Yunali V.; Wu, Zhuo-Xun; Zeng, Leli; Lei, Zi-Ning; Teng, Qiu-Xu; Ashby, Charles R.; Guan, Yingjun; Chen, Zhe-Sheng (Frontiers in Oncology, 2020)
The efficacy of anti-cancer drugs in patients can be attenuated by the development of multi-drug resistance (MDR) due to ATP-binding cassette (ABC) transporters overexpression. In this in vitro study, we determined the reversal effect of EGFR inhibitor sapitinib in colorectal cancer SW620 and SW620/Ad300 cells that overexpresses ABCB1, non-cancer HEK293/pcDNA3.1 and ABCB1 transfected HEK293 cells. Sapitinib significantly sensitized paclitaxel and doxorubicin in ABCB1 overexpressing cells without altering the expression or the subcellular location of the ABCB1 transporter. Sapitinib significantly increased the accumulation of [3H]-paclitaxel in SW620/AD300 cells probably via stimulating ATPase activity which could competitively inhibit the uptake of [3H]-paclitaxel. Furthermore, sapitinib inhibited the growth of resistant multicellular tumor spheroids (MCTS). The docking study indicated that sapitinib interacted with the efflux site of ABCB1 transporter by π-π interaction and two hydrogen bonds. In conclusion, our study suggests that sapitinib surmounts MDR mediated by ABCB1 transporter in cancer cells.